An Unusual Case of Pulmonary Alveolar Microlithiasis Masquerading as Pulmonary Tuberculosis - Nadia Ilyas; Sandhya Poflee; Vedita Bobde; Satish Helwatkar (Asian Journal of Medical Research, 2019)
Pulmonary Alveolar Microlithiasis (PAM) is a rare chronic lung disease characterized by bilateral intra-alveolar calcium and phosphate deposition throughout the lung parenchyma. PAM is known to occur over wide age range. Exact etiopathogenesis of PAM is not known and long term survival is uncertain. Patient can be asymptomatic or present with progressive pulmonary symptoms. Radiological features of PAM are pathognomic for radiologist who is aware of this rare pulmonary disease. However the changes of PAM on imaging can be misdiagnosed as those due to pulmonary tuberculosis which is a relatively common diagnosis in the Indian setting. Definitive diagnosis is based on typical microscopic features seen on transbronchial or open lung biopsy.We report a case of 41 years old female who was treated as a case of pulmonary tuberculosis for two years without relief of symptoms at a peripheral medical centre. Final diagnosis of PAM was made on the basis of characteristic radiological findings and microscopic features at our Institute.